Ultrasound guided peripheral nerve block as alternative to subarachnoid block in total hip replacement arthroplasty: a retrospective study - Rayamajhi, Anuj Jung; Paudel, Prashanta; Paudel, Subash Chandra; Dhungel, Bidur Kumar; Yadav, Rupesh Kumar (Journal of Chitwan Medical College, 2019)
Background: Ultrasound guided peripheral nerve blocks have become increasingly popular in the lower limb orthopaedic and gaining more acceptances in total hip replacement surgeries too. The main objective of this study was to compare peripheral nerve block and spinal anesthesia for total hip replacement surgeries. Methods: In this retrospective study, total patients that underwent total hip replacement in our institution during specific time period were included for the study. They were divided into spinal and peripheral nerve block groups, and data were collected for the analysis. USG guided lumbar plexus, sacral plexus, superior gluteal nerve block was done and conventional landmark technique was done for spinal group. Mean arterial blood pressure, total fluid consumption, total fentanyl consumption, pain scores and incidence of nausea was compared. Results: We included 43 patients for the study in which 23 patients were included in nerve block group, and 20 patients in the spinal group. In compared to spinal group, nerve block group had more stable mean arterial blood pressure (P <0.05), less total fluid consumption (P=.000), lower pain scores and fentanyl consumption (P <0.05), and less incidence of nausea (4% to 20%). Conclusions: Peripheral nerve block can be good alternative to spinal anesthesia for total hip replacement surgeries, with more hemodynamic stability and better pain management along with less opioid and fluid consumption.